Evaluation of Internet Search Engines: Methodological Issues and Assumptions - Spiteri, Louise F.; Richard, Nathalie (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper examines two questions: what methodological assumptions underlie existing evaluations of Internet search engines and how do they differ from those used to study information retrieval systems (IRSs)? an examination of 31 Internet-based studies reveals that they employ a methodology very similar to the experimental model that has been used to evaluate IRSs; in other words, the . . .